2013
DOI: 10.2319/040813-271.1
|View full text |Cite
|
Sign up to set email alerts
|

Mini-implant stability at the initial healing period: A clinical pilot study

Abstract: Mini-implant stability is subject to changes during the healing process. During weeks 3 and 4, a significant decrease of the stability was observed. After 4 weeks, the stability did not change significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 26 publications
1
20
0
9
Order By: Relevance
“…Type A and Type C exhibited no significant correlation between IT and RF in both tests. Therefore, our finding is similar to that of Nienkemper et al [19], implying that higher IT does not significantly contribute to higher RF. Type A exhibited a significant correlation between IT and RT in the 90 and 45 tests.…”
Section: Mini-implantssupporting
confidence: 92%
See 1 more Smart Citation
“…Type A and Type C exhibited no significant correlation between IT and RF in both tests. Therefore, our finding is similar to that of Nienkemper et al [19], implying that higher IT does not significantly contribute to higher RF. Type A exhibited a significant correlation between IT and RT in the 90 and 45 tests.…”
Section: Mini-implantssupporting
confidence: 92%
“…However, we found that the types with a smaller anchor area had lower RT values. Nienkemper et al [19] investigated the relationship between IT and RF and reported no significant correlation between them. In the present study, Type B exhibited a significant correlation between IT and RF in the 90 test.…”
Section: Mini-implantsmentioning
confidence: 99%
“…Therefore, there is still controversy that mechanical forces (IT, RF, and RT) depend upon the material composition and shape of orthodontic microimplants. Nienkemper et al [15] reported that no significant correlation existed between the IT and RF. In the correlation analysis of the present study, the IT, RF, and RT were not significantly correlated in both the vertical and horizontal directions; therefore, our results are consistent with those of Nienkemper et al [15].…”
Section: Discussionmentioning
confidence: 97%
“…Nienkemper et al [15] reported that no significant correlation existed between the IT and RF. In the correlation analysis of the present study, the IT, RF, and RT were not significantly correlated in both the vertical and horizontal directions; therefore, our results are consistent with those of Nienkemper et al [15]. This implies that the IT cannot be used to infer the RF (primary stability), and similarly, the RF cannot be used to infer the RT.…”
Section: Discussionmentioning
confidence: 97%
“…The impact of insertion site on stability was evaluated by comparison to a control group with median inserted mini‐implants of the same size from a previous pilot study (Nienkemper et al. ).…”
mentioning
confidence: 99%